Erythema annulare centrifugum: hypersensitivity reaction to Ascaris lumbricoides? - Chiriac, A. (European Journal of Pediatric Dermatology, 2019)
The term “figurate erythema” is an umbrella that indicates numerous clinical conditions that are not very different from each other in terms of clinical and histological morphology. It can be practically caused by most of the genetic and environmental factors responsible for skin disorders (2). Erythema marginatum rheumaticum, erythema chronicum migrans of borreliosis and erythema gyratum repens are the most characteristic ones, not so much for morphology and histological findings, but for the responsible causes. In most cases of figurate erythema the cause is not obvious and must be searched by medical history and laboratory tests. When a cause is hypothesized, as in the actual case, one cannot always be sure of its responsibility. Rare reports of the literature (1) and the eosinophilia of histological examination favor the possible parasitic etiology of erythema annulare centrifugum.